Anmeldelse af Pia Virtanen: Zur Geschichte der finnisch-deutschen Lexikographie 1888-1991. Studien zur Makrostruktur - Martola, Nina (LexicoNordica, 1994)
The purpose of the book is on one hand to give a short review of the history of Finnish-German lexicography and its present state. In this respect it is quite successful. On the other hand it presents its readers with an empirical experiment of how to investigate, compare and evaluate the macrostructure in a couple of dictionaries. In reality the investigation is concemed with the lemmas rather than the whole macrostructure. The results presented are of no greater value statistically on account of the modest number of words included, but the method shown is interesting and could be useful if applied to larger masses of words. Anmeldt værk: Pia Virtanen: Zur Geschichte der finnisch-deutschen Lexikographie 1888-1991. Studien zur Makrostruktur. Studien zur zweisprachigen Lexikographie 1. red. Herbert Ernst Wiegand. Germanistische Linguistik 114. Olms. Hildesheim 1993